PENYELESAIAN SISTEM PERSAMAAN LINEAR DENGAN GENERALISASI METODE JACOBI - Sandra Roza; M. Natsir; Asli Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Jacobi's method is an iterative method to solve a system of linear equations Ax = b.  If A is a strictly diagonally dominant matrix, Jacobi's method always converges to a solution Ax = b. In this paper,we develop the generalized Jacobi'smethod; by changing, one of the splitting matrices has to be in the form of a bandage diagonal matrix. By assumption that A is a strictly diagonally dominant matrix, we show that the generalized Jacobi's method is always convergent to a solution Ax = b.